Intervening in the β-barrel structure of lipid binding proteins: Consequences on folding, ligand-binding and aggregation propensity - Curto, Lucrecia María (2015)
Natural β-folds manage to fold up successfully. By contrast, attempts to dissect fragments or peptides from well folded β-sheet proteins have met with insurmountable difficulties. Here we briefly review selected successful cases of intervention on the well-known scaffold of intestinal fatty acid binding protein (IFABP). Lessons from these examples might set guidelines along the design of proteins belonging to this class. Impact of modifications on topology, binding and aggregation is highlighted. With the aid of abridged variants of IFABP we focus on key structural features responsible for the assembly into oligomeric forms or aggregates.